Studies on the syntheses of β-carboline alkaloids brevicarine and brevicolline - Batizi, Benedek; Pollák, Patrik; Dancsó, András; Keglevich, Péter; Simig, Gyula; Volk, Balázs; Milen, Mátyás (Beilstein Journal of Organic Chemistry, 2025)
A new total synthesis of the β-carboline alkaloid brevicarine is disclosed. The synthesis was carried out starting from an aromatic triflate key intermediate, allowing the introduction of various substituents into position 4 of β-carboline by cross-coupling reactions. Thanks to its scalability, this novel approach ensures a broad accessibility to the target compound for potential pharmacological measurements. Using detailed NMR studies, the NMR signals have been assigned for both the base and its dihydrochloride salt for further confirming their structures. A new synthesis of the related alkaloid brevicolline was also attempted from the same intermediate. However, after successful coupling of β-carboline with N-methylpyrrole, the trials to saturate the pyrrole ring under various conditions led to unexpected reactions: reduction of ring A of the β-carboline skeleton or trifluoroethylation of the pyrrole moiety occurred, leading to interesting and potentially useful derivatives.
Keywords: alkaloid; β-carboline; Carex brevicollis DC; cross-coupling reaction; trifluoroethylation